Type 2 Diabetes, PNPLA3 rs738409 Polymorphism, and the Risk of Liver Cirrhosis: Analysis of Taiwan Biobank - Hsueh, Kuan-Chun; Nfor, Oswald Ndi; Hsu, Shu-Yi; Yang, Shun-Fa; Liaw, Yung-Po (Frontiers in Genetics, 2022)
Type 2 diabetes (T2D) and liver cirrhosis remain significant public health threats in Taiwan. These conditions are reported to be associated with the rs738409 polymorphism of the patatin-like phospholipase domain-containing protein 3 gene (PNPLA3) in European populations. We assessed the effect of T2D and PNPLA3 rs738409 polymorphism on liver cirrhosis among Taiwan Biobank (TWB) participants. In total, 17,985 participants in TWB had their health records linked to the National Health Insurance Research Database (NHIRD). Participants included those who visited the assessment centers between 2008 and 2015, with an age range between 30 and 70 years of age. We performed logistic regression analysis to investigate the odds ratios (OR) for liver cirrhosis among participants based on the T2D status and rs738409 genotypes. Genotyping was performed using the Axiom Genome-Wide TWB Array Plate. In our analysis, 150 of the 17,469 eligible participants were identified as cirrhosis cases. Based on the univariate analysis, liver cirrhosis was positively associated with T2D (OR, 1.83; 95% CI 1.23 to 2.70) whereas, the variant rs738409 was not (regardless of the genetic model). The variant and T2D, however, showed significant interactions in the additive, genotype, and dominant models (p values of 0.0302, 0.0395, and 0.0455, respectively). We observed a statistically significant association between T2D and liver cirrhosis and variant rs738409 with an OR of 1.71 (95% CI, 1.03-2.84) for individuals carrying a G allele compared to those with a C allele and 2.92(95% CI 1.07-7.99) for GG compared to CC individuals. According to our study, Taiwanese adults with T2D and the rs738409 GG genotype are more likely to develop liver cirrhosis.